Sociological Research on Higher Education in English Canada 1970-1980: A Thematic Review - Pike, Robert M. (Canadian Journal of Higher Education, 1981)
Sociological research on higher education in Canada is in an infancy state at best. How- ever, this article explores some main ideological and empirical themes which are emerging in the relevant sociological literature on higher education in English Canada, concentrating primarily on the growing number of studies dealing with inequality of access to education beyond the high school, and particularly the search for the sources of inequality in socio- economic status, region and sex. Some attention is also given to the limited body of socio- logical research on higher education organizations, on student attitudes, values and behaviour, and on the academic profession in English Canada. The greater part of the English language literature is shown to emanate from Ontario and the major ideological thrust in this literature is noted as being a conflict perspective which emphasizes the role of conflict in the process of change within universities and colleges, and which perceives these institutions as agencies for the reinforcement of the status quo rather than for the moderation of existing social inequalities. Various suggestions are offered for future research priorities, emphasizing particularly the need for the employment of a developmental comparative perspective.